1956
DOI: 10.2466/pr0.1956.2.3.91
|View full text |Cite
|
Sign up to set email alerts
|

The Rewarded, the Unrewarded, the Chosen, and the Unchosen

Abstract: One object was presented alone for two trials and then paired with a second object for six trials. Next, the second object was paired with a third object for six trials, and then sometimes the third object was paired with a fourth object for six trials. Four such sequences were given to seven test-wise rhesus monkeys on each of five days. Retention tests involving pairing of the dicrimination objects with new objects occurred on three days. When a chosen correct or incorrect object was paired with a new object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1965
1965
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…The C-D trials seem very much like partially reinforced PA trials (give that C is nonreinforced in the B-C pair) that occur in the context of D-E, which resembles an NA trial. Leary (1956Leary ( , 1958 appeared to have anticipated value transfer in his early studies of ambiguous-cue performance by monkeys. He found that choice of the rewarded object on the first trial of a discrimination task induced a preference for the S object relative to a novel object, and that this was not simply a familiarity effect.…”
Section: Discussionmentioning
confidence: 99%
“…The C-D trials seem very much like partially reinforced PA trials (give that C is nonreinforced in the B-C pair) that occur in the context of D-E, which resembles an NA trial. Leary (1956Leary ( , 1958 appeared to have anticipated value transfer in his early studies of ambiguous-cue performance by monkeys. He found that choice of the rewarded object on the first trial of a discrimination task induced a preference for the S object relative to a novel object, and that this was not simply a familiarity effect.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the associative processes linking responses to cue values that signal reward and to those that signal nonreward are not equivalent. Indeed, learning which cue values signal reward is virtually all that is learned: very little aversiveness (often the opposite) accrues to the negative stimulus (see also Leary, 1956: Behar, 1962. From this argument, given the very rapid learning that occurred and assuming that both color and form analyzers are at asymptote, the animal first identifies the cue value that signals reward.…”
Section: Positivementioning
confidence: 99%
“…However, even in sophisticated monkeys, avoidance of the negative stimulus is absent unless the animal has actually responded to it (Behar, 1962;leary, 1956). The negative stimulus which has not been responded to, when paired with a neutral stimulus, is preferred at levels well above chance expectation.…”
mentioning
confidence: 99%